Pugicorn and Hugicorn - Rose Mtailda (London; Hodder Children's Books, 2022)
It's summer in Twinkleton-Under-Beanstalk, and Princess Ava and her magical pet Pugicorn are helping out at Mrs Paws' Pupicorn Training School! The excitable pups must discover their rainbow powers in order to graduate at the end of the week. But one little pupicorn is more interested in hugs and cuddles than listening and learning... Can Princess Ava and Pugicorn help Hugicorn find her powers in time? An adorable adventure, full of magic and friendship, with a gentle message about everyone learning at their own pace
Keywords: Children's stories